Peripartum cardiomyopathy. - Gama Pinto, Catarina (2008)
The Peripartum Cardiomyopathy is a rare form of heart disease, of uncertain etiology, more common in black and multiparous women, older than thirty years old. Is defined as development of maternal congestive heart failure, in the last month of pregnancy or within five months after delivery, with documented left ventricular systolic dysfunction, in the absence of a demonstrable cause for heart failure in a previously healthy woman. The diagnosis is commonly established with chest radiography, electrocardiogram and echocardiography. Treatment consist in medical therapy with inotropic support, afterload and preload redution, and anticoagulation. Surgical care with cardiac transplantation is indicated in severe cases with progressive left ventricular dysfunction, despite medical therapy. Prognosis seems dependent on recovery of left ventricular function and maternal mortality rates could reach 50%. Future pregnancy is not recommended in woman with persistent ventricular dysfunction. The authors present a case report in a black nuliparous woman at term, with 33 years old, without previous heart disease that presents a sudden heart failure, with ventricular dysfunction on echocardiography, after the caesarean, with recovery of normal ventricular function at 11th day of puerperium.